Influence of the pre-operative time in upright sitting position and the needle type on the incidence of post-dural puncture headache (PDPH) in patients receiving a spinal saddle block for anorectal surgery - Schmittner, Marc; Urban, Nicole; Janke, Andrea; Weiß, Christel; Bussen, Dieter G.; Burmeister, Marc-Alexander; Beck, Grietje (International journal of colorectal disease, 2011)
A spinal saddle block can be a safe method for anorectal surgery with a low rate of complications when performed with the right technique. A dreaded complication is the post-dural puncture headache (PDPH), which can be decreased by the use of non-cutting spinal needles. Regrettably, cutting Quincke (Q)-type needles are still widely used for economic reasons. Besides size and design of a spinal needle, the pre-operative time in upright sitting position may also influence the incidence of PDPH after spinal saddle block.
Published: 22 July 2010
Gesehen am 12.10.2022